Soil compaction of peat under the influence of electrokinetic stabilization (EKS) treatment - Abdul Hadi, Abdul Wahab (2019)
This study aims to enhance the properties of peat such as, (shear strength, compressibility, permeability and liquid limit). Peat is considered as one of the problematic soil in construction projects all over the world, which covers about 4% land of the whole world while 8% of the total area of Malaysia and about (5.86%) of peat soil existing in Johor state. Low shear strength of peat may lead to massive loss of various sectors contributing toward any economic activities such as construction & agriculture projects. There are several issues related to peat stabilization which has become a priority to ensure that soft soil is stable & capable of supporting a load after treated by a suitable soil stabilization method. The problem can be finally reduced by applying stabilization treatment to enhance its properties. One of the known technique Electrokinetic Stabilization treatment, by applying an electric potential to stabilize soft soil. In this method, aluminum was used as an electrode with various voltage potential in the range of 110 to 150 V was applied on both cathode and anode electrode for the duration of 3 and 6 hours at the testing condition without & with a load of (50 kg). Soil parameters such as, shear strength (